Critical Discourse of the Chinese Rebellion in Indonesian History Textbook - Kurniawan, Hendra; Supriatna, Nana; Mulyana, Agus; Yulifar, Leli (Diakronika, 2023)
This study aims to reveal the discourse practices in the narrative of the Chinese Rebellion in the Indonesian History textbook. Having long disappeared from Indonesian historiography, the Chinese-Javanese alliance against the VOC, often called Geger Pacinan (1740-1743), has reappeared in history textbooks. Its presence needs to be studied to understand the discourse practices that are to be conveyed by the narratives that are constructed. This study's subject was the Chinese Rebellion text in the Indonesian History textbook for class XI SMA based on the 2013 Curriculum published by the Ministry of Education and Culture of the Republic of Indonesia in 2017. The Critical Discourse Analysis (CDA) method, according to Teun A. van Dijk, was used to analyze the dimensions of the text, social cognition, and the social context of the narratives that are the research subject. The result is that the report in the text dimension does not present the Chinese role through the history of the event as a whole. In the size of social cognition, it is found that there is a potential to strengthen the practice of discourse, which leads to the marginalization of the Chinese role. The social context dimension has not entirely shifted from the New Order paradigm, which harbored stereotypes against the Chinese. In conclusion, the text of the Chinese Rebellion requires the teacher’s role to make the deconstruction process in learning history meaningful for students, especially in internalizing the value of diversity for national integration.